ANALISA DAYA REKAT CAT PADA PROSES PAINTING DENGAN VARIASI PARAMETER DUST LEVEL, TEMPERATUR, DAN KEKASARAN PERMUKAAN MENGGUNAKAN METODE TAGUCHI - Yahya Bahar Prihantono; Pranowo Sidi; Farizi Rachman (Proceedings Conference On Design Manufacture Engineering And Its Application, 2020)
PT. Lintech Duta Pratama is one of the contracting companies in Indonesia that produces various kinds of needs in various industries. PT Lintech Duta Pratama uses finishing materials using paintings as a deterrent to corrosion. At the material level and surface roughness of the material to the optimal adhesion of paint on steel plate A in the painting process. This study uses an experimental design using the Taguchi method with 3 levels and 3 parameter factors, based on the Taguchi method 27 experiments were conducted. Then the paint adhesion test is done, the test is done using the cut test corss method. This study aims to determine the paint adhesion in accordance with company specifications and determine the process of painting for the paint adhesion of the test object with a combination of parameter variations tested. Must minimize painting defects. The results of the analysis showed that the dust level parameter had a significant effect on the response of paint adhesion, but the surface roughness and temperature parameters did not have a significant effect. As a combination of parameters that can optimize the paint adhesion response are dust level with level 1, temperature with 26 ° C, and surface roughness with 40 µm.